The politics of affective societies an interdisciplinary essay - Bens, Jonas 1985-; Diefenbach, Aletta; John, Thomas; Kahl, Antje 1979-; Lehmann, Hauke 1981-; Lüthjohann, Matthias; Oberkrome, Friederike; Roth, Hans; Scheidecker, Gabriel 1982-; Thonhauser, Gerhard 1984-; Ural, Nur Yasemin; Wahba, Dina; et al. (transcript, 2019)
Many recent academic and semi-academic voices claim that political deliberation has become exceedingly affective and hence destabilizing. Approaching the question from a wide range of angles, the authors of this interdisciplinary essay remain sceptical that it is really increased affectivity that constitutes the symptom of our times. They propose instead to reframe the debate by deploying the analytic of affective societies - claiming that affect and emotion are in fact present in all social interaction. What changes over time and place are not, then, the absence or presence of affect and emotions, but rather the modes and calibrations of affective and emotional registers. In this manner, this essay works towards a theory of affect and the political
Erscheint als Open Access bei De Gruyter
Keywords: Affekt; Politische Entscheidung; Affect; Emotion; Culture; Cultural Theory; Ethnology; Cultural Anthropology; Cultural Studies; Aufsatzsammlung